BS EN 2995-006. Aerospace series. Circuit breakers, single-pole, temperature compensated, rated currents 1 A to 25 A. Part 006. 6, 3 mm & 2, 8mm blade terminal. With polarized signal contact. Product standard (28th November 2019) - British Standards Institution,
No abstract available